1997
DOI: 10.2307/1551985
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Active-Layer Thickness over a Large Region: Kuparuk River Basin, Alaska, U.S.A.

Abstract: Active-layer thickness was mapped over a 26,278-km2 area of northern Alaska containing complex and highly variable patterns of topography, vegetation, and soil properties. Procedures included frequent probing to ascertain thaw depth in representative land-cover units, extensive thermal monitoring with data loggers, and application of spatial analytic techniques. Geographic information systems technology was used analytically to merge thaw-depth and temperature data with a digital land-cover map, a digital elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
205
2
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(221 citation statements)
references
References 55 publications
8
205
2
2
Order By: Relevance
“…In the foothills a fixed-interval design sufficient to resolve the scale of maximum variability on the 1 km 2 grids would require far more effort than could reasonably be expended. Other methods, such as hierarchical sampling and analysis [Webster and Oliver, 1990;Walker and Walker, 1991] or stratification by land cover category [Nelson et al, 1997b;Muller et al, 1998], should be used to assess spatial variability in such situations. Given the large number of sample points on the ARCSS grids, however, the 100 m spacing appears adequate to obtain summary statistics that can be used to track long-term changes in active-layer thickness for the entire area [Fagan, 1995].…”
Section: Discussionmentioning
confidence: 99%
“…In the foothills a fixed-interval design sufficient to resolve the scale of maximum variability on the 1 km 2 grids would require far more effort than could reasonably be expended. Other methods, such as hierarchical sampling and analysis [Webster and Oliver, 1990;Walker and Walker, 1991] or stratification by land cover category [Nelson et al, 1997b;Muller et al, 1998], should be used to assess spatial variability in such situations. Given the large number of sample points on the ARCSS grids, however, the 100 m spacing appears adequate to obtain summary statistics that can be used to track long-term changes in active-layer thickness for the entire area [Fagan, 1995].…”
Section: Discussionmentioning
confidence: 99%
“…The Arctic is undergoing rapid changes in temperature and snow-melt dates [22,23]. Here we examine responses of two Arctic-breeding migratory songbirds the Lapland longspur, Calcarius lapponicus, and Gambel's white-crowned sparrow, Zonotrichia leucophrys gambelii to 'extreme' conditions in spring of 2013 on the North Slope of Alaska.…”
Section: Case Studies: Arctic-breeding Songbirds Species Level Variamentioning
confidence: 99%
“…These extreme conditions resulted in reduced body condition in both Lapland longspurs and white-crowned sparrows as they arrived on the breeding grounds [24]. In addition to cold springs, shifts in climate are resulting in greater occurrence of snowfall during the critical period of egg laying and incubation [22,24]. Although these events might not always be classified as extreme according to the climatological definition, they do present challenges that may be perceived as extreme by the birds that are enduring them.…”
Section: Case Studies: Arctic-breeding Songbirds Species Level Variamentioning
confidence: 99%
“…(2009) showed variations around the mean for one site of around 50 %. Nelson et al (1997) reported extreme local variations in ALT, based on terrain and soil moisture conditions; for example they found a difference in ALT of 50 % between an acidic and non-acidic tundra site. Similarly, differences in the terrain lead to differences in observed ALT of 20 cm from one observation grid (1 km 2 ) to the next.…”
Section: Model Evaluationmentioning
confidence: 99%